A novel model of acquired hydrocephalus for evaluation of neurosurgical treatments - James P. McAllister (BMC, 2021)
Abstract Background Many animal models have been used to study the pathophysiology of hydrocephalus; most of these have been rodent models whose lissencephalic cerebral cortex may not respond to ventriculomegaly in the same way as gyrencephalic species and whose size is not amenable to evaluation of clinically relevant neurosurgical treatments. Fewer models of hydrocephalus in gyrencephalic species have been used; thus, we have expanded upon a porcine model of hydrocephalus in juvenile pigs and used it to explore surgical treatment methods. Methods Acquired hydrocephalus was induced in 33–41-day old pigs by percutaneous intracisternal injections of kaolin (n = 17). Controls consisted of sham saline-injected (n = 6) and intact (n = 4) animals. Magnetic resonance imaging (MRI) was employed to evaluate ventriculomegaly at 11–42 days post-kaolin and to plan the surgical implantation of ventriculoperitoneal shunts at 14–38-days post-kaolin. Behavioral and neurological status were assessed. Results Bilateral ventriculomegaly occurred post-induction in all regions of the cerebral ventricles, with prominent CSF flow voids in the third ventricle, foramina of Monro, and cerebral aqueduct. Kaolin deposits formed a solid cast in the basal cisterns but the cisterna magna was patent. In 17 untreated hydrocephalic animals. Mean total ventricular volume was 8898 ± 5917 SD mm3 at 11–43 days of age, which was significantly larger than the baseline values of 2251 ± 194 SD mm3 for 6 sham controls aged 45–55 days, (p < 0.001). Past the post-induction recovery period, untreated pigs were asymptomatic despite exhibiting mild-moderate ventriculomegaly. Three out of 4 shunted animals showed a reduction in ventricular volume after 20–30 days of treatment, however some developed ataxia and lethargy, from putative shunt malfunction. Conclusions Kaolin induction of acquired hydrocephalus in juvenile pigs produced an in vivo model that is highly translational, allowing systematic studies of the pathophysiology and clinical treatment of hydrocephalus.